Comparison of Fecal DNA Extraction Kits for the Giant Panda (Ailuropoda melanoleuca) by Short Tandem Repeat Genotype Analysis - Jie Gao; Chunhai Li; Yitao Wu; Xinyong Zhu; Siqin Liu; Yang Zhang; Huizhong Pang; Jiaheng Li; Jiawen Liu; Wangsheng Zhao; Ye Wang; Jie Kou (Ecology and Evolution)
ABSTRACT Genetic analysis of short tandem repeat (STR) loci using noninvasive fecal samples is currently the most widely used method in genetic surveys of giant pandas (Ailuropoda melanoleuca). However, low‐quality fecal DNA obtained from fecal samples may affect the accuracy of short tandem repeat (STR) genotyping results and pose a challenge to accurately identify individuals. The aim of this study was thus to compare the efficiency of DNA extraction kits in obtaining high‐quality fecal host DNA from giant panda fecal samples. In this study, six commercial kits widely used in fecal DNA extraction, the QIAamp Fast DNA Stool Mini Kit (Q kit), Beaver Beads Stool DNA Kit (H kit), Mag‐MK Soil & Stool Genome DNA Extraction kit (S kit), Magnetic Soil And Stool DNA Kit (T kit), E.Z.N.A Mag‐Bind Stool DNA Kit (O kit) and Mag Beads Fast DNA Kit for Feces (M kit) were compared. Fecal DNA concentration and purity were measured, and STR genotyping was performed using blood and fecal DNA from captive giant pandas to compare the genotype matches at 11 STR loci. Our results show that the most efficient extraction kits were the Q and T kits, and the Q kit had a greater ability to remove PCR inhibitors than other kits. Careful selection of DNA extraction kits is required to achieve optimal genotyping accuracy across different STR genotyping systems. For STR genotyping systems with smaller PCR product sizes (< 200 bp, such as GPL‐29, GP‐08, GP‐01, Panda‐40 and Panda‐05), all six kits demonstrated high genotype matching rates (GMR > 80%). In contrast, for STR genotyping systems with longer PCR product sizes (> 200 bp), the choice of DNA extraction kit significantly influenced GMR, with the H kit and O kit performing well for gpy‐5 but the Q kit and O kit being less suitable for GPL‐08.